2008 National Radio Science Conference 2008
DOI: 10.1109/nrsc.2008.4542383
|View full text |Cite
|
Sign up to set email alerts
|

Development of a computer-aided classification system for cancer detection from digital mammograms

Abstract: Mammogram-breast x-ray is considered the most effective, low cost, and reliable method in early detection of breast cancer. Although general rules for the differentiation between benign and malignant breast lesion exist, only 15 to 30% of masses referred for surgical biopsy are actually malignant. Computer-Aided Classification system was used to help in diagnosing abnormalities faster than traditional screening program without the drawback attribute to human factors. In this work, an approach is proposed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…These solutions can be classified into classical and deep learning models. Early CAD systems have been developed using the classical machine learning models such as the research conducted in [18][19][20][21][22][23][24][25][26][27][28][29][30]. The basic framework in these studies consists of three stages including Region of Interest (ROI) extraction, feature extraction and selection, and classification stage using well-known classifiers such as K Nearest Neighbor (KNN), Support Vector Machine (SVM), Neural Network (NN), and Ensemble classifiers such as the work conducted by Kadah et al [18,21,24,25,31].…”
Section: Related Workmentioning
confidence: 99%
“…These solutions can be classified into classical and deep learning models. Early CAD systems have been developed using the classical machine learning models such as the research conducted in [18][19][20][21][22][23][24][25][26][27][28][29][30]. The basic framework in these studies consists of three stages including Region of Interest (ROI) extraction, feature extraction and selection, and classification stage using well-known classifiers such as K Nearest Neighbor (KNN), Support Vector Machine (SVM), Neural Network (NN), and Ensemble classifiers such as the work conducted by Kadah et al [18,21,24,25,31].…”
Section: Related Workmentioning
confidence: 99%
“…Data mining techniques have also revealed unknown causes and helped in detecting breast cancer. Alolfe et al [11] used k-NN algorithm from the extracted features to classify if a particular region of interest (ROI) of the digital image, an output of mammogram, is carrying benign or malign masses to determine breast cancer and reported that the algorithm at k = 1 gave the best result. Abreu et al [12] tried to find out overall survival rate for woman, suffering from breast cancer using 3 ensemble methods (TreeBagger, LPBoost and Subspace) considering 25% missing data and found Treebagger with 3 neighbor was the best among the above three methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First we study the designing of classification methodologies for electronic health records, a well studied problem for many diseases e.g. heart disease [6,7,8,9,10], breast cancer [11,12,13], etc. (ref section 1.1).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the largest ROI size provides the worst detection while the best results were obtained for middle size ROI of size 512×512 pixels and proposed multi size analyses for further improvement. Alolfe et al (2008) selected an ROI of size 256×256 pixels from the mammograms in order to extract features and to classify normal and cancerous breast tissue. The results were less satisfactory due to small number of cases used in learning phase and due to variation in mammogram database.…”
Section: Literature Surveymentioning
confidence: 99%